Deficit in attentional capture by social-value related conditioned stimuli — a new perspective to understand the social-reward learning disorders among individuals with depressive symptoms - Hu, Jinsheng; Zhao, Xiaoning (Frontiers in Psychiatry, 2026)
ObjectivesThis study investigated social-reward learning disorders in individuals with depressive symptoms by examining attentional resources to be captured by social-value related conditioned stimuli.MethodsWe utilized a modified additional singleton paradigm in which the prominent distractor was characterized by a stimuli associated with large- or small- social value. In Study 1, 49 participants with minimal depressive symptoms(BDI-II ≤ 13 & dimension of depressive symptoms on the SCL-90-R ≤ 2.10) and 49 with obvious depressive symptoms(BDI-II ≥ 14 & dimension of depressive symptoms on the SCL-90-R > 2.10) were included in the control and depressed groups, respectively. They were asked to find the response target and make a judgment related to the target by conducting a keypress response. In Study 2, 55 participants with obvious depressive symptoms and 54 with minimal depressive symptoms were asked to fixate on the target as quickly as possible.ResultsIn the keypress response task, regarding the influence on response time, the interference effect of large-value distractors in the depressed group was significantly less than that in the control group. In the fixation-response task, compared with the control group, participants of the depressed group also showed less bias of oculomotor capture by social-value distractors.ConclusionsFor individuals with depressive symptoms, insufficient interference of social-value distractors was revealed both in the manual response and eye-tracking tasks. Those with depressive symptoms displayed deficits in attentional resources to be captured by social-value related stimuli.